2007
DOI: 10.1080/13651820601090596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cell salvage autotransfusion utility during liver transplantation

Abstract: Despite increased blood loss in period 2, CS saved 21 g/L of Hb per patient or two RBC unit transfusions. As long as we cannot predict with accuracy which patients will bleed, we will continue to use the CS for all OLTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 22 publications
1
66
0
Order By: Relevance
“…practice in different institutions [117] . Obviating the need for at least 2 units of allogenic RBC delivers a cost-benefit and therefore ACS is likely to be financially viable in major blood loss surgery where transfusion is expected.…”
Section: Donohue CI Et Al Reducing Transfusion Requirements In Livementioning
confidence: 99%
“…practice in different institutions [117] . Obviating the need for at least 2 units of allogenic RBC delivers a cost-benefit and therefore ACS is likely to be financially viable in major blood loss surgery where transfusion is expected.…”
Section: Donohue CI Et Al Reducing Transfusion Requirements In Livementioning
confidence: 99%
“…Muscari et al [117] reported no difference in the incidence of neoplastic recurrence with the use of cell saver during liver transplantation for hepatocarcinoma. Various authors also confirm that the use of cell salvage is useful to reduce the exposure to allogenic blood during liver transplantation for hepatocellular carcinoma and is cost-effective as well [95,115] . Filtration through leucodepletion filters in association with irradiation (25 Gy) prior to transfusion of recovered blood has also been proposed to increase the safety of blood salvaging procedure in cancer surgery [118] .…”
Section: Blood Salvaged From Patients With Liver Tumormentioning
confidence: 99%
“…However, when compared with the cost of providing allogenic blood, it becomes cost effective when at least two or more units of blood can be salvaged and reinfused. Massicotte et al [95] demonstrated that when cell salvage autotransfusion was used systematically for every patient (75 OLTx) there was enough blood salvage to retransfuse 65% of the cases; in their centre with a low transfusion rate, it saved a mean of 21 g/L of Hb per patient or two RBC unit transfusions.…”
Section: Blood Salvage During Oltxmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important surgical measure to reduce perioperative blood product transfusions is use of intraoperative cell salvage (CS). In a prospective survey conducted by Massicotte et al [43] in patients undergoing LT, the use of CS was associated with saving two RBCs unit transfusions per patient and thus also reducing costs. Nowadays, however, as an increasing amount of transfusion-free LTs are performed, a "stand by" set up rather than routine application of CS is recommended [34].…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%